A descriptive semantics of modelling process catering for whole product parametric. Issue 2 (April 2017) - Ge, Xiao-Bo; Shao, Xiao-Dong; Li, Shen; Wang, Dou
Abstract: To date, the entire product parametric technology has made great progress to significantly improve product design efficiency. However, the technology uses an established modelling process, which makes it very difficult to adapt to changing product requirements. A method that can be customised for the whole machine is discussed in this paper; this method is intended to increase the adaptability of the entire product parametric technology. First, a frame model concept is proposed based on an analysis of a large number of product modelling processes. Second, a semantic model for describing the modelling process is proposed, and its instantiation is studied. Next, according to the semantics of the modelling process, a product parametric modelling system is established. Finally, based on an examination of the electronic module modelling, it was found that modelling efficiency increased significantly.